Masturbation parameters: their relation to sexual arousal in young people who engage in same-sex relationships - Sánchez-Pérez, Gracia M.; Granados, Reina; Mangas, Pablo; Sierra, Juan Carlos (Frontiers in Psychology, 2025)
BackgroundInterest in masturbation in sexual orientation and gender diversity research are rather limited. Extending this research field to include this type of population by considering different masturbation parameters is necessary. In this respect, various masturbation parameters (i.e., negative attitudes toward masturbation, solitary sexual desire, current masturbation frequency, subjective orgasm experience) were validated in a laboratory study with different measures of sexual arousal in persons who engage in same-sex relationships.AimOur main aim was to provide evidence to support the validity of the different masturbation parameters in young people who engage in same-sex relationships. The association between masturbation parameters and various sexual arousal measures (genital response, rating of sexual arousal and rating of genital sensations) was analyzed.MethodsDuring a lab task, 72 young adults who engaged in same-sex relationships (36 women, 36 men; age range: 18–32 years) watched content-neutral and sexually explicit films. They included scenes of self-exploration and solitary masturbation behaviors performed by individuals of the same sex as the participants. Negative attitudes toward masturbation, solitary sexual desire, current masturbation frequency, dimensions of subjective orgasm experience in the solitary masturbation context (i.e., affective, sensory, intimacy, rewards), propensity for sexual excitation, genital response (i.e., penile circumference and vaginal pulse amplitude), rating of sexual arousal and rating of genital sensations were assessed. Regression models were conducted to explain the arousal measures with masturbation parameters.ResultsIn women, the intimacy dimension of the subjective orgasm experience in masturbation (β = 0.42, p = 0.007) and solitary sexual desire (β = 0.32, p = 0.040) predicted the rating of sexual arousal by explaining 24.1% of its variance. Conversely for men, the rewards dimension of the subjective orgasm experience in masturbation (β = 0.40, p = 0.016) significantly predicted genital response and explained 13.4% of its variance.ConclusionOur findings validate some examined masturbation parameters (specifically solitary sexual desire and subjective orgasm experience) in young adults who engage in same-sex relationships. Gender differences in the masturbation parameters were observed for the relevance of these masturbation parameters for explaining sexual arousal. These findings support the relation between masturbation and sexual function.